Effect of water absorption and hydroxyapatite addition on mechanical and microstructural properties of dental luting cements - Elibol, Cagatay; Atalay, Ender Goksen; Sagir, Kadir; Yoruc, Afife Binnaz Hazar (WALTER DE GRUYTER GMBH, 2022)
In recent years, dental cements have gained more and more importance due to the increasing clinical expectations. They are used as restorative materials and as materials providing critical functions such as chemical and physical adhesion in restorations and protective lining in the cavity. In this work, the effect of water absorption on the mechanical and microstructural properties of different commercial dental cements is systematically investigated. Furthermore, the effect of addition of biocompatible hydroxyapatite on the mechanical and microstructural properties of the cements is characterized. The results show that Voco Meron containing glass ionomer provides the highest values in water absorption and volume change tests. Ketac Cem Radiopaque (209 HV) containing glass ionomer exhibits the highest hardness increase after immersion for 28 days in water, whereas the highest water uptake value is observed in Adhesor Carbofine cement containing zinc polycarboxylate. The hardness of Adhesor ZincPhospate increases with increasing content of hydroxyapatite, whereas in Ketac Cem Radiopaque, the hardness decreases with increasing content of hydroxyapatite significantly. Test results are verified by microstructural analysis of different types of dental cements using scanning electron microscopy and the effect of particle size/distribution on the properties that are of crucial clinical importance is characterized in detail.
Keywords: dental cements; hardness; hydroxyapatite; microstructural analysis; water absorption; Materials Science